Можливості ревіталізації промислових територій міст на прикладі вулиці Замкової у місті Львові - Боднар, Тарас; Ясінський, Максим; Bodnar, Taras; Yasinskyi, Maksym (Видавництво Львівської політехніки, 2023)
Ревіталізація промислових територій є важливою складовою ефективного розвитку міст. Така практика уже поширена в багатьох країнах світу. В Україні є не багато реалізованих об’єктів, але щороку їх стає більше. В статті розглядається практичний досвід ревіталізації з інших країн та виокремлено застосовані підходи. Спільні та відмінні для різних проектів. Проведено дослідження промислової території на вулиці Замковій, у Львові. Авторами виділено складні питання у розвитку території та сформовано власні принципи для ефективного розвитку ділянки. Акцентується на: необхідності використання міжнародного досвіду для впровадження в Україні найкращих проектів з уникнення багатьох проблем та необхідності подальшого дослідження питання ревіталізації промислових територій міст.

Globally, cities have two options for growth: extensive and intensive. The former involves expanding the city's area to accommodate increased development or population. However, this option has significant drawbacks, including longer travel times within the city, loss of arable or recreational land around the city, and the need to construct new infrastructure. As a result, many cities opt for the intensive approach, which maximizes land use efficiency. The topic of revitalization has been under investigation since the mid-20th century, but it is relatively new for Ukraine. As a result, there is a lack of scientific articles that thoroughly explore the subject from all angles. From Ukrainian authors, I want to highlight Hnatiuk L., Melnyk M., Sych O., Levchenko O., Birkentale V. The aim of this article is to examine the global practices of breathing new life into industrial areas. Additionally, it will delve into the history and present state of an industrial area located on Zamkova Street in Lviv. The article seeks to identify the development prospects of the region and provide recommendations and principles for the revitalization of Zamkova Street. We have discovered a few examples of international projects that showcase the importance of experience: KingKros in London, UK, HafenCity in Hamburg, Germany, and Two Kings in Toronto, Canada. As part of our research, we have identified some challenges facing the industrial area on Zamkova Street. Based on our analysis of these challenges and similar projects, we have created a list of principles for revitalization. These include mixed-use buildings, height restrictions, infrastructure development, the idea of a "five-minute city" or "city of short distances," a broad range of housing prices, ample public spaces, new points of attraction, job opportunities close to homes, architecture competitions, preservation of historical buildings, emphasis on pedestrian safety, and the concept of a "sponge city." The issue of industrial areas in Ukrainian cities is complex, but not unique. Many cities have gone through this developmental phase. Fortunately, our cities have an opportunity to draw from successful revitalization experiences. By tailoring these practices to fit each unique situation, we can transform our communities for the better.
Possibility of industrial areas revitalization in the example of Zamkova street in Lviv, Ukraine
Keywords: природне світло; сакральний простір; сакральна архітектура; храм; композиція; модернізм; revitalization; development; industrial areas; pulic space; reconstruction; multifunctionality; 725